Impact of gut microbiota structure in heat-stressed broilers - Shi, Dayou; Bai, Lin; Qu, Qian; Zhou, Shanshan; Yang, Meimei; Guo, Shining; Li, Qiuhong; Liu, Cui (Poultry science, 2019)
Gut microbiota** play important roles in the health and disease status of both humans and animals. Little is known about whether heat stress changes the composition of the gut microbiota in chicken. The aim of this study was to investigate the effects of heat stress on changes in caecal microbiota, including changes in growth performance as well as HSP70 and cortisol levels. Sixty 14-day-old female broilers were equally divided into 2 treatment groups with different housing temperatures for 28 D: a control group (C) at 24 to 26°C and a heat stress (HS) group at 34 to 38°C. The caecal contents of the broiler chicken were then extracted on days 1, 3, 7, 14, and 28. Genomic DNA was extracted and amplified based on the V3∼V4 hypervariable region of 16S rRNA high-throughput sequence analyses. The results showed that the average daily gain and average daily feed intake were significantly decreased and that the feed conversion ratio was increased by heat stress. The concentrations of HSP70 and cortisol in the serum were significantly increased. The composition of gut microbiota was influenced by heat stress** through beta diversity analysis and taxon-based analysis. In particular, at the phylum level the composition of Firmicutes, Tenericutes, and Proteobacteria in HS group was increased than that of C group, and Bacteroidetes and Cyanobacteria in HS group were reduced than that of C group. In addition, the composition of Anaeroplasma and Lactobacillus phyla in HS group were increased than that of C group, whereas the Bacteroides, Oscillospira, Faecalibacterium, and Dorea genera in HS group were decreased than that of C group. In conclusion, the gut microbiota in broilers were changed by heat stress. And the changes of the gut microbiota could provide the basis for further research on the heat stress.